The efforts to improving locomotor movement skills through traditional Gobak Sodor methods - Kurniawan, Farel; Junaidi, Slamet; Weda (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This research is based on the results of researchers' observations that the PJOK learning process at SDIT AL ARIF, Gampengrejo District, still faces obstacles, especially a lack of creativity in less effective learning. This research aims to determine the increase in students' skills and learning outcomes in locomotor movements through the traditional Gobak Sodor game method. This research uses the classroom action research (PTK) method which is carried out in two cycles, with two meetings in each cycle using teacher observation, student observation, and student learning outcome tests. The subjects of this research involved fifth-grade students at SDIT AL ARIF consisting of 13 male students and 10 female students, a total of 23 students. The research results prove that the traditional game Gobak Sodor can improve students' locomotor skills. This can be seen from the assessment of the balance aspect in cycle I, which was 47% complete and 53% incomplete. In cycle II, the completion results increased to 100% and 0% incomplete. The agility aspect in cycle I was 43.3% complete and 56.7% incomplete, increasing to 100% complete in cycle II. The speed aspect in cycle I was 47% complete and 53% incomplete, increasing to 100% complete in cycle II.